1985
DOI: 10.1021/i200029a002
|View full text |Cite
|
Sign up to set email alerts
|

Separation of gold cyanide ion from anion-exchange resins

Abstract: use in three-phase systems and on the development of a comprehensive model to predict mass transfer in vertical bubble flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The first condition studied was temperature. The optimum operating temperature for the original gold recovery process had been determined to be 45 °C (Law et al, 1985), and since elution rate generally increases with increasing temperture, there was no need to attempt regeneration at a lower temperature. Although the maximum operating temperature of the IRA-900C resin is quoted as being 60 °C for processes involving hydroxide (Rohm and Haas Co., 1981), running the column at this temperature for regeneration produced an unacceptable capacity loss and a physical texture change which was attributed to breakdown of the resin.…”
Section: Eluentmentioning
confidence: 99%
See 1 more Smart Citation
“…The first condition studied was temperature. The optimum operating temperature for the original gold recovery process had been determined to be 45 °C (Law et al, 1985), and since elution rate generally increases with increasing temperture, there was no need to attempt regeneration at a lower temperature. Although the maximum operating temperature of the IRA-900C resin is quoted as being 60 °C for processes involving hydroxide (Rohm and Haas Co., 1981), running the column at this temperature for regeneration produced an unacceptable capacity loss and a physical texture change which was attributed to breakdown of the resin.…”
Section: Eluentmentioning
confidence: 99%
“…In an effort to find a simpler and more environmentally sound method for recovering gold from ion-exchange re- sins, Law (1982Law ( ,1983) and Law et al (1985) developed a process by which gold can be eluted from the resin and recovered directly as potassium gold cyanide (Law and Gabriel, 1986). The eluent, consisting of a concentrated KSCN solution in a mixed solvent of water and DMF, is fed to the gold-containing resin column.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, Felix et al [2] and Lu et al [3] have suggested an electrochemical process to destroy cyanide and recover copper at the same time. Xie et al [4] and Law et al [5] employed the anion-exchange techniques as a selective recovery method of cyanide-metal complexes from cyanide waste streams. In addition, a copper cyanide recovery process using activated carbon has also been proposed [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nonaqueous solvents have been investigated for many years as a way of altering selectivities in both cation- and anion-exchange processes. It has been demonstrated that mixtures of water and organic solvents are more effective than aqueous solutions for the separation of [Au(CN) 2 ] - from ion-exchange resin. , Dipolar polar aprotic solvents such as dimethylformamide, N -methyl-2-pyrrolidone, and acetone are particularly well suited for this purpose. Furthermore, the elution can be carried out with simple counterions such as Cl - and SCN - .…”
Section: Introductionmentioning
confidence: 99%